2019
DOI: 10.1021/acs.orglett.9b02107
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Nazarov Cyclization-Based Chirality Transfer for Asymmetric Synthesis of 2-Cyclopentenones

Abstract: Asymmetric synthesis of 2-cyclopentenones was achieved by chirality transfer based on Lewis acid catalyzed decarboxylative Nazarov cyclization of optically active cyclic enol carbonates, which are prepared by silver-catalyzed carbon dioxide incorporation into optically pure propargyl alcohols. The stereochemistry at the 4,5-positions of the 2-cyclopentenones was cleanly constructed by reflecting the stereochemistry of the starting materials. This method could be applied to various substrates to obtain the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Compounds 2a – 2t contain quaternary carbon centers, which are challenging to build otherwise in synthesis . Note that the carbonate with better electron-donating group ( 1i or 1t ) is relatively less stable, and some cyclopentenones derived from Nazarov-type reactions ( 4i and 4t , Figure ) could be observed when standing in the air for some time; this type of transformation has been previously detailed by Yamada and co-workers . Specifically, the furan-substituted carbonate 1u was converted in situ into the cyclopentenone 4u during the carbonate synthesis stage (Figure ).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Compounds 2a – 2t contain quaternary carbon centers, which are challenging to build otherwise in synthesis . Note that the carbonate with better electron-donating group ( 1i or 1t ) is relatively less stable, and some cyclopentenones derived from Nazarov-type reactions ( 4i and 4t , Figure ) could be observed when standing in the air for some time; this type of transformation has been previously detailed by Yamada and co-workers . Specifically, the furan-substituted carbonate 1u was converted in situ into the cyclopentenone 4u during the carbonate synthesis stage (Figure ).…”
mentioning
confidence: 73%
“…Specifically, the furan-substituted carbonate 1u was converted in situ into the cyclopentenone 4u during the carbonate synthesis stage (Figure ). The introduction of an extra phenyl ( 1v ) or methyl ( 1w ) group on the vinyl group of the carbonate is feasible, although ketone products ( 4v or 4w ) were isolated quantitatively under the optimized conditions similar to the performance of cyclohexyl-substituted substrate 1x (Figure ). In contrast, the use of CF 3 -substituted carbonate 1y gave rise to a complex reaction mixture, although it is much more stable compared to carbonate 1v ; this indicates an electronic effect on the stability and reactivity of the carbonate substrate.…”
mentioning
confidence: 99%
“…On the other hand, decarboxylative chemistry has gained much research interest mainly due to the advantages of ambient reaction conditions, friendly operations, and only CO 2 -byproduct generation. , Some of us previously reported that a water nucleophilic attack of a Pd-allyl intermediate derived from the decarboxylation of vinyl cyclic carbonate A proved to be a fantastic approach to access a batch of polysubstituted allylic alcohols with exclusive ( Z )-configuration (Scheme a) . Taking into account the synthetically important and challenging synthesis of stereodefined polysubstituted alkenes, this water nucleophilic approach represents a great step forward toward ( Z )-configured polysubstituted allylic alcohols.…”
mentioning
confidence: 99%
“…It appears that C1–C4 is arrayed in a relatively rigid curve, with only the arene ring free to rotate about C3–C4. If the system aligns during ionization as shown in J , with the C5 carbon opposite the C1 oxygen, the generated helically chiral pentadienyl cation (see 3a ) can only rotate in one direction. As such, the chirality of reactant 2a is largely retained throughout the ionization/cyclization process, even though the point chirality at C1 of 2a is lost. These findings suggest that the kinetic barrier for cyclization of 3a to 4a is slightly lower than the barrier for conformational inversion of 3a to epi - 3a , with the minor isomer epi - 5 resulting from cyclization and rearomatization of epi - 3a .…”
mentioning
confidence: 99%